2016
DOI: 10.1097/md.0000000000003663
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Benefits of Dual Antiplatelet Therapy Beyond 12 Months After Coronary Stenting

Abstract: The optimal duration of dual antiplatelet therapy (DAT) after coronary stenting remains poorly define. The aim of this study was to evaluate the impact of longer than 24 months DAT in patients who received drug-eluting and bare-metal stents.A total of 1010 individuals who underwent elective, urgent or emergency coronary angioplasty with intended stent implantation at reference or specialized cardiac hospitals were randomized to receive long-term and short-term DAT to determine the benefits and adverse effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…Data from these two trials were obtained from published study protocols and conference presentation files available at the Transcatheter Cardiovascular Therapeutics MD website sponsored by the Cardiovascular Research Foundation (https://www.tctmd.com). We excluded studies that did not report outcomes of interest in the ACS subgroup …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from these two trials were obtained from published study protocols and conference presentation files available at the Transcatheter Cardiovascular Therapeutics MD website sponsored by the Cardiovascular Research Foundation (https://www.tctmd.com). We excluded studies that did not report outcomes of interest in the ACS subgroup …”
Section: Resultsmentioning
confidence: 99%
“…17,18 We excluded studies that did not report outcomes of interest in the ACS subgroup. 2,[19][20][21] The baseline characteristics of included studies are shown in Table 1. Among the 10 trials, 3 trials exclusively enrolled ACS patients.…”
Section: Resultsmentioning
confidence: 99%
“…Известно, что при проведении длительной терапии антиагрегантными препаратами наблюдается развитие такого побочного эффекта, как кровотечения. Наиболее часто развиваются кровотечения, которые наблюдаются в системе желудочно-кишечного тракта, а также не редки проявления внутричерепных кровоизлияний, вследствие чего происходит увеличение риска ишемических событий [25][26][27][28].…”
Section: Discussionunclassified
“…Of 11 studies, nine (7,(12)(13)(14)(15)(16)(17)(18)20) reported the outcome of all-cause mortality. Overall mortality events in these studies were 3,422 (4.48%) of 76,310 patients.…”
Section: Efficacy Outcomes 321 All-cause Mortalitymentioning
confidence: 99%